Navigating the Gluten-Free Boom: The Dark Side of Gluten Free Diet - Lerner, Aaron; O'Bryan, Thomas; Matthias, Torsten (Frontiers in Pediatrics, 2019)
In gluten dependent conditions the gluten free diet is the cornerstone of therapy, decreasing disease activity, improving health and quality of life and treating or preventing the associated complications. Gluten withdrawal implies strict and lifelong elimination not only of wheat, barley, rye and wheat-contaminated oats, but also of numerous non-nutritional products where components of wheat are often added. Due to multiple reasons the diet is difficult to follow and the long-term adherence is decreased with time. The present review summarizes the dark side of gluten restriction where nutritional deficiencies, toxicity, morbidity, mortality and mental health problems are reported. The aim being to increase awareness, avoid, detect and treat the side effects and to promote a healthier nutrition, for the patient’s benefits.